Creating holistic technology-enhanced learning experiences : tales from a future school in Singapore - Tay, Lee Yong; Lim, Cher Ping (Other Books., 2013)
Creating Holistic Technology-Enhanced Learning Experiences: Tales of a Future School in Singapore Editors: Lee Yong TAY & Cher Ping LIM The global level of economic, ecological, social, political and cultural integration across nation states and the rapid advancement of technology have brought about transformations that are part of globalisation. Our students are expected to be agents of change rather than passive observers of world events; and at the same time, to live together in an increasingly diverse and complex society and to reflect on and interpret fast changing information. In such a new world order, the holistic development of our students, namely in the cognitive, aesthetics, physical, social and moral, leadership and global domains, is pivotal. This edited book provides descriptive and interpretive accounts of how an elementary school in the FutureSchools@Singapore programme creates holistic technology-enhanced learning experiences for its students at the classroom and school levels. By documenting these accounts and linking them to student learning outcomes, the school will lead the way in providing possible models for the seamless and pervasive integration of information and communication technologies (ICT) into the curriculum for the holistic development of our students.